Conceptual considerations for the understanding of environmental management in the public sector (First part) - Johnson-Madrigal, Helmut (2012)
Along the modernity arose several perceptions on the matter of Environmental Management, in response to the particular vision of its proponents. The current reality requires a new perception more comprehensive and complex in the light of the need to meet social, economic, political, cultural and environmental needs; all essential components for the implementation of a model of sustainable development more ethical, moral, fair and equitable.